Together - Oliver, Jamie, 1975- (Flatiron Books, 2021)
"Welcome friends and family back around your table with Jamie Oliver's brand-new cookbook, Together - a joyous celebration of incredible food to share. Being with our loved ones has never felt so important, and great food is the perfect excuse to get together. Each chapter features a meal, from seasonal feasts to curry nights, with a simple, achievable menu that can be mostly prepped ahead. Jamie's aim - whether you're following the full meal or choosing just one of the 130 individual recipes - is to minimize your time in the kitchen so you can maximize the time you spend with your guests. Jamie's Together also helps to take the stress out of cooking by arming you with tips, tricks, and hacks to stay organized and get ahead of the game. Inspirational but practical, Together is about comfort, celebration, creating new memories, and, above all, sharing fantastic food. This is about memorable meals, made easy. Let's dig in - together!"--